(3GdCZGfjs - (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj, J (B356 (3g` s
(3ChdgG (B:s
(3CNHGQ CHj fNjdI hfSHg s
(3BNQgG (B:s
(3jfJgi CKfGA CNHGQ GdbMja hfSHg Hbhdg (B: (3TGYQ ebd ef TYQGA GdESdGe s
(3GdfSNI HgG MhGTs
(3LGA ai UaMI GdYfhGf HChd GdcJGH agQSJ HCSeGA GdeJQLejf ai gPG GdSaQ hdcfg jMJhi Ydi CSeGA ZjQ ehLhOg ai GdcJGH JeKd KdK gPG GdagQSJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdCOHs